2013
DOI: 10.1002/dvg.22722
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA methylation between two wing phenotypes adults of Sogatella furcifera

Abstract: Sogatella furcifera is a major rice pest with wing dimorphism. DNA methylation is an important epigenetic modification that plays a role in gene regulation and phenotype variation in most organisms. The objective of the current research was to survey the frequencies and variation of cytosine methylation at CCGG sequences in macropterous female adults (MFA) and brachypterous female adults (BFA) of S. furcifera, and to determine the occurrence of methylation changes associated with wing phenotypes by using methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…There are also known genes responsible for wing patterning and development in model organisms such as Drosophila melanogaster, which may be relevant to intra-specific wing polymorphism 58 . While genetic changes often underlie wing polymorphism,epigenetic changes have also been demonstrated between wing morphs in a planthopper (Sogatella furcifera) 59,60 .…”
Section: Introductionmentioning
confidence: 99%
“…There are also known genes responsible for wing patterning and development in model organisms such as Drosophila melanogaster, which may be relevant to intra-specific wing polymorphism 58 . While genetic changes often underlie wing polymorphism,epigenetic changes have also been demonstrated between wing morphs in a planthopper (Sogatella furcifera) 59,60 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that phenotypic differences can be explained as methylation differences between individuals (Johnson & Tricker, ; Bonasio et al ., ; Weiner & Toth, ; Zhou et al ., ). The two forms examined in the present study only can be distinguished by body coloration until the female deutonymphs become adults.…”
Section: Discussionmentioning
confidence: 99%
“…In social insects, cytosine methylation has a critical role in caste specialization (Kucharski et al ., ; Bonasio et al ., ; Weiner et al ., ). In agricultural pests, DNA methylation is the potential cause of the different morphs of green aphids (Dombrovsky et al ., ), and the different wing phenotypes between macropterous and brachypterous females of the white‐backed planthopper (Zhou et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Genomic DNA methylation in S. furcifera was first investigated in our laboratory in relation to wing phenotype variation (Zhou et al, 2013). Given the importance of adult sex determination, in the present study, we examined the genomic DNA methylation patterns in adult male and female S. furcifera using methylation-sensitive amplification polymorphism (MSAP) analysis, so as to further explore the nature of insect sexual dimorphism from the perspective of epigenetics.…”
Section: Introductionmentioning
confidence: 99%